Does COVID-19 increase risk of stroke? (Annals of Medical Research, 2022)
Aim: In this study, it was aimed to compare the epidemiological characteristics and frequency of patients diagnosed with stroke in Kayseri City Hospital in the pre-COVID-19 pandemic period and during the COVID-19 pandemic and investigate whether COVID-19 increases the frequency of stroke.The true relationship between COVID-19 and the incidence of stroke has yet to be determined.Materials and Methods: A meta-analysis study reported that 1.4% (95%CI: 1.0–1.9) of 108,571 patients with COVID-19 developed acute cerebrovascular disease (CVD). Additionally, although the number of hospital admissions due to clinical presentation of suspected stroke decreased due to the pandemic, it has been suggested that the COVID-19 infection itself may cause a stroke.Results: In the literature, there have been reports of patient groups who developed ischemic stroke 1-2 weeks after diagnosis with typical COVID-19 symptoms, as well as patient groups who developed symptoms such as fever, dry cough, and shortness of breath during follow-up with ischemic stroke and who were subsequently diagnosed with COVID-19 . It was observed that patients presented with sudden onset loss of strength showing side without typical COVID-19 symptoms (such as cough, fever), and thoracic CT scans of these patients in the later period revealed pulmonary findings.Conclusion: In other words, COVID-19 patients may present with neurological symptoms such as acute cerebrovascular disease as the first symptom.
Keywords: COVID 19; Stroke; Pandemic period; Neurological symptoms; Acute cerebrovascular disease; Epidemiological characteristics